Resilience and Affiliate Stigma Among Parents of Children with Autism Spectrum Disorder: The Mediating Role of Life Satisfaction and the Moderating Role of Ostracism - Chen H; Ding Y; Xu D; Xiong Z (Psychology Research and Behavior Management, 2025)
Hanyu Chen,1,* Ying Ding,2,* Dongchen Xu,1 Zhiheng Xiong3 1School of Rehabilitation Sciences, Jiangsu Provincial Key Constructive Laboratory of Special Children’s Impairment and Intervention, Nanjing Normal University of Special Education, Nanjing, People’s Republic of China; 2Bio-X Institutes, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 3School of Humanities, Southeast University, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiheng Xiong, Email xzh_psy@seu.edu.cnPurpose: Parents of children with autism spectrum disorder (ASD) often encounter multifaceted challenges when addressing their children’s special needs. While existing studies have examined the relationship between parental resilience and mental health in this population, the underlying mechanisms governing this association remain poorly understood. The present study aims to investigate the association between parental resilience and affiliate stigma, examine the mediating role of life satisfaction in this relationship, and assess the moderating effect of ostracism on these pathways.Methods: This study employed a cross-sectional design to examine the relationship between resilience and affiliate stigma among parents of children with ASD, as well as the underlying mechanism. A total of 380 caregivers were recruited from autism intervention centers in Jiangsu Province, mainland China. Participants voluntarily completed questionnaires including the Brief Resilience Scale, the Affiliate Stigma Scale, the Satisfaction With Life Scale, and the Ostracism Short Scale.Results: (1) Resilience of parents of children with autism negatively predicted affiliate stigma; (2) Life satisfaction partially mediated the relationship between resilience and affiliate stigma; and (3) Ostracism significantly moderated the relationship between life satisfaction and affiliate stigma.Conclusion: This study reveals the complex relationship between resilience, affiliate stigma, life satisfaction, and ostracism among parents of children with ASD. It highlights the significance of enhancing parental resilience, improving life satisfaction, and reducing ostracism in alleviating the stress of affiliate stigma in families of children with autism. In the family support system for children with ASD, it is necessary to build an inclusive social environment and provide resources for psychological interventions to enhance parents’ resilience in the face of challenges.Keywords: resilience, affiliate stigma, life satisfaction, ostracism